Enacting a critical translingual approach in teacher preparation: Disrupting oppressive language ideologies and fostering the personal, political, and pedagogical stances of preservice teachers of English. Issue 2 (3rd February 2022) - Seltzer, Kate
Abstract : This article builds on García, Johnson, and Seltzer's (2017) concept of a translanguaging stance and lays out three of its interrelated elements—the personal, the political, and the pedagogical—that can position teachers of English to disrupt oppressive language ideologies. To move from an overemphasis on "practice" toward a focus on stance development requires that teacher preparation programs engage majority white, monolingual teacher candidates in critical reflection on how ideologies around being white and monolingual shape their perceptions of language‐minoritized students' languaging and literacies. This article offers practical approaches rooted both in theory and in collaborative research with a classroom English teacher to explore how teacher preparation programs can integrate self‐reflective, consciousness‐raising activities and projects into their coursework to encourage candidates to grapple with these three elements of their teaching stance.